2020
DOI: 10.1177/1352458520941493
|View full text |Cite
|
Sign up to set email alerts
|

Mapping white matter damage distribution in neuromyelitis optica spectrum disorders with a multimodal MRI approach

Abstract: Background: The pathogenetic mechanisms sustaining neuroinflammatory disorders may originate from the cerebrospinal fluid. Objective: To evaluate white matter damage with diffusion tensor imaging and T1/T2-weighted ratio at progressive distances from the ventricular system in neuromyelitis optica spectrum disorders and multiple sclerosis. Methods: Fractional anisotropy, mean, axial, and radial diffusivity and T1/T2-weighted ratio maps were obtained from patients with seropositive neuromyelitis optica spectrum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 38 publications
6
21
0
1
Order By: Relevance
“…We believe that these effects are minimized in the current cohort for the following reasons: (1) we used CAT12 for segmentation, which corrects for partial volume effects; 34 (2) we reran the analysis using eroded tissue masks and the linear mixed model results remained stable; and (3) we show that, in this cohort, the scaling factor is not influenced by disease factors and that the T1w and T2w gray matter intensities are not sensitive to pathology, confirming previous findings. 14 In addition, the findings that sT1w/T2w are correlated with lesion volume is consistent with recent publications using the conventional T1w/T2w and T1w/T2w corrected using cerebrospinal fluid, 12 , 35 further supporting the similarity of these methods. Nonetheless future studies investigating sT1w/T2w over time in healthy controls as well as studies specifically designed to further investigate the impact of gray matter pathology on the validity of the calibration are necessary to help interpret the results presented here.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…We believe that these effects are minimized in the current cohort for the following reasons: (1) we used CAT12 for segmentation, which corrects for partial volume effects; 34 (2) we reran the analysis using eroded tissue masks and the linear mixed model results remained stable; and (3) we show that, in this cohort, the scaling factor is not influenced by disease factors and that the T1w and T2w gray matter intensities are not sensitive to pathology, confirming previous findings. 14 In addition, the findings that sT1w/T2w are correlated with lesion volume is consistent with recent publications using the conventional T1w/T2w and T1w/T2w corrected using cerebrospinal fluid, 12 , 35 further supporting the similarity of these methods. Nonetheless future studies investigating sT1w/T2w over time in healthy controls as well as studies specifically designed to further investigate the impact of gray matter pathology on the validity of the calibration are necessary to help interpret the results presented here.…”
Section: Discussionsupporting
confidence: 87%
“…sT1w/T2w is a relatively novel measure of NAWM integrity damage in MS, standardizing the conventional T1w/T2w using the combined image technique, originally developed for contrast enhancement. 13 The conventional T1w/T2w has been shown to be sensitive to MS pathology, both in the cortex 32 and NAWM, 11 , 12 , 15 and is related to reduced EDSS and cognitive impairment. 11 , 32 The main benefit of the conventional T1w/T2w compared to other markers of NAWM damage is that it uses routine clinical images and has relatively simple post-processing steps.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 135 137 Diffusion tensor imaging is another advanced MRI technique that has been used to evaluate microstructural changes in the normal-appearing white matter in NMOSD and has demonstrated that the white matter injury in NMOSD is diffuse, compared with MS in which the white matter alterations are predominantly periventricular. 16 , 138 In addition, microstructural white matter changes have been identified in the afferent visual pathway in NMOSD patients with a history of optic neuritis, as well as in NMOSD patients with a history of LETM without optic neuritis. 16 , 139 Diffusion tensor imaging has also been used to explore the differences in microstructural parenchymal damage between NMOSD and MOGAD and has shown that, compared with healthy controls, it is more prominent in MOGAD patients than in NMOSD patients, while brain volume loss is more severe in NMOSD patients.…”
Section: Should Mri Inform Treatment Decision-making In Nmosd?mentioning
confidence: 99%
“…An example of multiparameter MRI is conventional T 2 -weighted imaging (T 2 WI), which is mainly affected by tissue water composition and can sensitivity detect inflammation and edema in tissues 4 , 6 . Moreover, in regions with dense myelin, such as the corpus callosum (CC), the signal intensity of T 2 WI is inversely proportional to the myelin content 7 . Susceptibility-weighted imaging (SWI) mainly reflects the magnetic susceptibility of tissues in a magnetic field 8 , 9 .…”
Section: Introductionmentioning
confidence: 99%